Basic protocols for Drosophila S2 cell line: maintenance and transfection - Ceriani, Maria Fernanda (2007)
Cells in culture have been increasingly employed in the dissection of intracellular processes. They are generally easier to handle than the organism of study and certainly less complex, which facilitates testing for specific functions and protein-protein interactions. This chapter will describe the extremely simple steps required to keep a healthy S2 cell culture going